2022
DOI: 10.1002/jev2.12269
|View full text |Cite
|
Sign up to set email alerts
|

Proviral role of human respiratory epithelial cell‐derived small extracellular vesicles in SARS‐CoV‐2 infection

Abstract: Small Extracellular Vesicles (sEVs) are 50–200 nm in diameter vesicles delimited by a lipid bilayer, formed within the endosomal network or derived from the plasma membrane. They are secreted in various biological fluids, including airway nasal mucus. The goal of this work was to understand the role of sEVs present in the mucus (mu‐sEVs) produced by human nasal epithelial cells (HNECs) in SARS‐CoV‐2 infection. We show that uninfected HNECs produce mu‐sEVs containing SARS‐CoV‐2 receptor ACE2 and activated prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The ECVs in the nasal cavity assist in the intracellular furin‐mediated prefusion of SARS‐CoV‐2 spike protein during viral entry. This mechanism is mainly performed by vesicular TMPRSS2 activity, which makes SARS‐CoV‐2 more likely to enter target cells via the “early,” TMPRSS2‐dependent pathway, rather than the “late,” cathepsin‐dependent pathway 29 . The SARS‐CoV spike protein's interaction with the ACE2 receptor has been demonstrated to be blocked by the cleavage of ACE2 by the disintegrin and metalloproteinase domain‐containing protein 17 (ADAM17) 30 .…”
Section: Exosomes and Sars‐cov‐2mentioning
confidence: 99%
See 1 more Smart Citation
“…The ECVs in the nasal cavity assist in the intracellular furin‐mediated prefusion of SARS‐CoV‐2 spike protein during viral entry. This mechanism is mainly performed by vesicular TMPRSS2 activity, which makes SARS‐CoV‐2 more likely to enter target cells via the “early,” TMPRSS2‐dependent pathway, rather than the “late,” cathepsin‐dependent pathway 29 . The SARS‐CoV spike protein's interaction with the ACE2 receptor has been demonstrated to be blocked by the cleavage of ACE2 by the disintegrin and metalloproteinase domain‐containing protein 17 (ADAM17) 30 .…”
Section: Exosomes and Sars‐cov‐2mentioning
confidence: 99%
“…This mechanism is mainly performed by vesicular TMPRSS2 activity, which makes SARS-CoV-2 more likely to enter target cells via the "early," TMPRSS2-dependent pathway, rather than the "late," cathepsin-dependent pathway. 29 The SARS-CoV spike protein's interaction with the ACE2 receptor has been demonstrated to be blocked by the cleavage of ACE2 by the disintegrin and metalloproteinase domain-containing protein 17 (ADAM17). 30 Tetraspanins (Tspans) are a class of transmembrane proteins that bind to other membrane-associated proteins to provide platforms necessary for viral entry.…”
Section: Exosomes and Sars-cov-2mentioning
confidence: 99%
“…Berry et al. also discovered evidence that EVs originating from the mucus of human nasal epithelial cells (mu‐sEV) increased SARS‐CoV‐2 infection of cells (Berry et al., 2022). They demonstrated that SARS‐CoV‐2 exists in both ‘closed’ or ‘open’ states and that, following SARS‐CoV‐2′s binding to ACE2 on mu‐sEV, the activated protease TMPRSS2 on mu‐sEV cleaves the S1/S2 boundary, exposing the structural domain of SARS‐CoV‐2 bound to the cell surface and leaving the S protein in an ‘open’ conformational state prior to fusion.…”
Section: Antagonism: Evs Antagonism With Sars‐cov‐2 Inspires Diagnosi...mentioning
confidence: 99%
“…Currently, the investigation of the virus and its long-term effects on lung health continues to be a priority due to its associated comorbidities, resulting in high mortality rates [ 2 ]. The primary infection initiation site is the epithelial mucosa of the upper respiratory tract and lungs, with a clinical presentation consisting of fever, cough, fatigue, and dyspnea [ 3 , 4 ]. SARS-CoV-2 is a 100 nm single-stranded RNA-enveloped virus.…”
Section: Introductionmentioning
confidence: 99%
“…Its entry into host cells depends on the binding of the viral (S) spike protein to the angiotensin-converting enzyme 2 (ACE2) receptor, which is mainly expressed in alveolar epithelial cells. Later, activation of serine protease TMPRSS2 leads to a cascade of reactions, triggering infection [ 4 , 5 ]. Recent studies have shown that the infectivity of SARS-CoV-2 is heavily dependent on endocytic mechanisms and has been shown to undergo rapid endocytosis in cells expressing abundant levels of ACE2 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%